Study on the correlation between dietary patterns and bone health among rural elderly people in Qingdao - Chang, Haoran; Han, Wenchao; Li, Jiafei; Jiao, Dazhi; Liu, Fangyu; Gao, Tianlin; Zhu, Wenjing; Gong, Jianbao (Frontiers in Nutrition, 2025)
ObjectiveTo evaluate the relationship between dietary patterns and bone health in the elderly, and to guide the elderly to establish a reasonable dietary pattern and improve bone health.MethodsThis cross-sectional study included 544 elderly individuals aged 60 and above in rural areas of Qingdao. Dietary patterns were analyzed using factor analysis. A logistic regression model was employed to assess the relationship between dietary patterns and osteoporosis. The correlation between body composition and T-score was analyzed using Spearman's rank correlation method in the R software.ResultsA total of four main dietary patterns were identified in this study, which included a balanced dietary pattern, a high-protein dietary pattern, a condiment dietary pattern, and a snack dietary pattern. After adjusting for potential confounding factors (age, residence status), it was found that a high-protein dietary pattern was positively correlated with bone health at the Q3 level (OR (95%CI) 0.435(0.190, 0.997), but not correlated at the Q4 level. The high-protein dietary pattern was significantly positively correlated with several body composition parameters, including intracellular fluid, extracellular fluid, total body water, protein, muscle mass, minerals, fat-free mass, skeletal muscle, left-hand muscle mass, right-hand muscle mass, and trunk muscle mass (all P < 0.05). Additionally, these body composition factors were positively correlated with osteoporosis T-scores.ConclusionThere is a correlation between dietary patterns and osteoporosis; a moderate amount of the high-protein dietary pattern is beneficial to the bone health of the elderly.